Constructing Housing Decisions in Later Life: A Discursive Analysis of Older Adults' Discussions about their Housing Decisions in New Zealand. Issue 4 (3rd July 2017) - Matthews, Tamyra; Stephens, Christine
Abstract: This study explores the social location of older New Zealanders' housing decisions by examining the discursive resources older adults draw on to construct their housing decisions. Housing decisions in later life are significant and complex, as the house in which an older person lives can be a central part of their life and impact on health, well-being, identity and belonging. While theoretical models exist to try understand these complex decisions for older adults, there are limited studies from a discursive perspective. Interviews were conducted with five individuals and two couples, aged over 65 years, who had made a range of different housing decisions. Using discourse analysis, five main interpretative repertoires that older adults used when talking about their housing decisions were identified, labelled: "Decline", "Medical", "Independence", "Stability" and "Family", along with the subject positions provided by each discursive resources. These findings are discussed in relation to discourses of ageing available in today's society.